Figures of bearded Bharavahakas on the capitals of the antarala - Temples of India Project Team (Jio Institute, 2024)
The dvarashakha (door jamb) of the central garbhagriha (sanctum sanctorum) in the Neelkanth Mahadev Temple is ornate. Seen here are details of the antarala (vestibule or antechamber) pilasters and the right side of the dvarashakha which has one main shakha (vertical band) with deities on it. The pilasters of the antarala have on their capitals bearded bharavahakas (load bearers).